Digitalization of Tourism in the Development of Samiran Tourism Village Based on Community Based Tourism in Selo, Boyolali - Hartini, Sri; Wulandari, Amy; Setiawan, Feri; Puspitasari, Ayu (LPPM Universitas PGRI Sumatera Barat, 2024)
Tourism digital transformation can make it easier for tourists to access all forms of information about tourism destinations. The digitalization of tourism is a step forward in responding to the current civilization of society which is oriented towards digital media in meeting the need for tourism. The aim of this research is to identify and analyze 1) the form of tourism digitalization that must be implemented in the development of Dewi Sambi; 2) Forms of community participation in supporting the development of Dewi Sambi Digitalization; and 3) Obstacles encountered in developing digitalization of Dewi Sambi tourism. The urgency of conducting this research is because tourism digitalization is a very important strategy as a means of providing information, introducing, communicating and promoting the beauty and uniqueness of Dewi Sambi so that it has an impact on the development of Dewi Sambi and the lives of its people. The development of digitalization is studied through Afnarius' Digital Tourism theory. This research uses a qualitative method with a PAR (Participatory Action Research) approach. Data collection techniques were carried out with involved participants (participant observation) and independent interviews This research resulted in 1) In developing the digitalization of tourist villages, Dewi Sambi Management and the community, both Homestay owners and Samiran Asri MSMEs, were able to implement and optimize the digital marketing media they currently have, such as websites, WhatsApp, Instagram, TikTok, Facebook and Google; 2) People try to actively use social media, take part in digital marketing training, and are willing to use paid WiFi every month; 3) The obstacles that arise in the development of tourism digitalization are the lack of public knowledge about digital marketing platforms and the lack of ability of the public to create media content. In the end, this research is expected to provide benefits to the community, the management of Dewi Sambi, and relevant stakeholders to be able to develop the digitalization of tourism.